Phytotoxic potential of Senna occidentalis and Senna obtusifolia - doi: 10.4025/actascibiolsci.v32i3.5833 - Peres, Marize Terezinha Lopes Pereira; Cândido, Ana Carina da Silva; Bonilla, Marilia Bisacotti; Faccenda, Odival; Hess, Sônia Corina (Acta Scientiarum. Biological Sciences, 2010)
This work aimed to investigate the phytotoxic potential of the aerial and underground parts of Senna occidentalis and S. obtusifolia on the germination and initial growth of lettuce and onion. Four concentrations were used of each ethanol extract (0, 250, 500 and 1000 mg L-1), with four replications of 50 seeds. From the investigated species, the aerial part of S. occidentalis interfered in onion germination and the aerial part of S. obtusifolia interfered in the germinations of lettuce and onion. The ethanol extract from the aerial and underground parts of the studied species inhibited the root growth of lettuce and onion. The hypocotyl/coleoptile growth in lettuce and onion was inhibited by the extract of S. obtusifolia aerial part and the underground part of S. occidentalisand S. obtusifolia. The results obtained make it possible to infer that the studied species contain substances that influence the germination and growth of the target seedlings.